Finding the concept, not just the word : a librarian's guide to ontologies and semantics - King, Brandy E.; Reinold, Kathy; ScienceDirect eBooks (Oxford : Chandos, 2008)
Aimed at students and professionals within Library and Information Services (LIS), this title is about the power and potential of ontologies to enhance the electronic search process.
Contents -- About the authors -- Preface -- Introduction -- Part 1: understanding ontologies -- Part 2: Semantic technologies -- Part 3: Case studies : theory and practice -- Part 4: Advanced topics -- Part 5: Transitions to the future -- Appendix -- Bibliography -- Index.
Includes bibliographical references (pages 181-198) and index.
Title fron PDF title page viewed on May29, 2013.
Elsevier
Keywords: Ontologies (Information retrieval); Semantic Web; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Ontologies (Information retrieval); Semantic Web; Electronic books